Localization of androgen-binding protein in proliferating Sertoli cells in culture. - Kierszenbaum, A L (1980)
The peroxidase and immunofluorescent localization patterns of androgen-binding protein (ABP), a biological marker of Sertoli cell function, have been examined in cultured Sertoli cells isolated from 20- to 22-day-old rats. ABP immunoreactivity in the form of cytoplasmic granules of variable diameter was observed in Sertoli cells with characteristic lipid droplets and a colony-forming, epithelial-like growth pattern. Incubation of cultures with [3H]thymidine demonstrated that Sertoli cells continue to produce ABP while retaining their capability for synthesizing DNA and undergoing mitosis. A variable number of cultured Sertoli cells became morphologically transformed after exposure to follitropin (follicle-stimulating hormone) and pharmacological agents acting on cyclic nucleotide metabolism. The induced change in Sertoli cell shape coincided with a disappearance of ABP-containing granules from the cytoplasm. These observations demonstrate that localization of ABP by immunological techniques is a valuable tool for the characterization of structural and functional properties of Sertoli cell in culture.